The Perception of the Legitimacy of Citizens' Assemblies in Deeply Divided Places? Evidence of Public and Elite Opinion from Consociational Northern Ireland. Issue 3 (26th July 2022) - Garry, John; Pow, James; Coakley, John; Farrell, David; O'Leary, Brendan; Tilley, James
Abstract: How much public and elite support is there for the use of a citizens' assembly – a random selection of citizens brought together to consider a policy issue – to tackle major, deadlock-inducing disagreements in deeply divided places with consociational political institutions? We focus on Northern Ireland and use evidence from a cross-sectional attitude survey, a survey-based experiment and elite interviews. We find that the general public support decision-making by a citizens' assembly, even when the decision reached is one they personally disagree with. However, support is lower among those with strong ideological views. We also find that elected politicians oppose delegating decision-making power to an 'undemocratic' citizens' assembly, but are more supportive of recommendation-making power. These findings highlight the potential for post-conflict consociations to be amended, with the consent of the parties, to include citizens' assemblies that make recommendations but not binding policy.